The Second Site Modifier, Sympathy for the ligule, Encodes a Homolog of Arabidopsis ENHANCED DISEASE RESISTANCE4 and Rescues the Liguleless narrow Maize Mutant. Issue 8 (19th June 2019) - Anderson, Alyssa; St. Aubin, Brian; Abraham-Juárez, María Jazmín; Leiboff, Samuel; Shen, Zhouxin; Briggs, Steve; Brunkard, Jacob O.; Hake, Sarah
Abstract : Allelic variation at Sympathy for the ligule affects growth and development of Liguleless narrow maize mutants. Abstract: Liguleless narrow1 encodes a plasma membrane-localized receptor-like kinase required for normal development of maize ( Zea mays ) leaves, internodes, and inflorescences. The semidominant Lgn-R mutation lacks kinase activity, and phenotypic severity is dependent on inbred background. We created near isogenic lines and assayed the phenotype in multiple environments. Lgn-R plants that carry the B73 version of Sympathy for the ligule ( Sol-B ) fail to grow under hot conditions, but those that carry the Mo17 version ( Sol-M ) survive at hot temperatures and are significantly taller at cool temperatures. To identify Sol, we used recombinant mapping and analyzed the Lgn-R phenotype in additional inbred backgrounds. We identified amino acid sequence variations in GRMZM2G075262 that segregate with severity of the Lgn-R phenotypes. This gene is expressed at high levels in Lgn-R B73, but expression drops to nonmutant levels with one copy of Sol-M . An EMS mutation solidified the identity of SOL as a maize homolog of Arabidopsis ( Arabidopsis thaliana ) ENHANCED DISEASE RESISTANCE4 (EDR4). SOL, like EDR4, is induced in response to pathogen-associated molecular patterns such as flg22. Integrated transcriptomic and phosphoproteomic analyses suggest that Lgn-R plants constitutively activate an immune signaling cascade that induces temperature-sensitive responses in addition to defects in leaf development. We propose that aspects of the severe Lgn-R developmental phenotype result from constitutive defense induction and that SOL potentially functions in repressing this response in Mo17 but not B73. Identification of LGN and its interaction with SOL provides insight into the integration of developmental control and immune responses.